2017
DOI: 10.18632/oncotarget.15594
|View full text |Cite
|
Sign up to set email alerts
|

Histamine therapeutic efficacy in metastatic melanoma: Role of histamine H4 receptor agonists and opportunity for combination with radiation

Abstract: The aims of the work were to improve our knowledge of the role of H4R in melanoma proliferation and assess in vivo the therapeutic efficacy of histamine, clozapine and JNJ28610244, an H4R agonist, in a preclinical metastatic model of melanoma. Additionally, we aimed to investigate the combinatorial effect of histamine and gamma radiation on the radiobiological response of melanoma cells.Results indicate that 1205Lu metastatic melanoma cells express H4R and that histamine inhibits proliferation, in part through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 66 publications
(87 reference statements)
2
34
0
2
Order By: Relevance
“…Histamine may be a crucial mediator in cancer development and progression. Its effects vary across cell types and depend on the balance between different receptor subtypes and its concentration within the tumour microenvironment (Massari et al ., ; Stoyanov et al ., ). Histamine levels in the plasma of NSCLC patients were found significantly decreased when compared with healthy controls (Della Rovere et al ., ), consistent with our results.…”
Section: Discussionmentioning
confidence: 98%
“…Histamine may be a crucial mediator in cancer development and progression. Its effects vary across cell types and depend on the balance between different receptor subtypes and its concentration within the tumour microenvironment (Massari et al ., ; Stoyanov et al ., ). Histamine levels in the plasma of NSCLC patients were found significantly decreased when compared with healthy controls (Della Rovere et al ., ), consistent with our results.…”
Section: Discussionmentioning
confidence: 98%
“…H 3 receptor activation has not been shown to modulate proliferation in human melanoma cells (Hegyesi et al ., 2005). However, H 4 receptors are functionally expressed in human melanoma cells, and the use of agonists, antagonists and siRNA demonstrated that the inhibitory effect of histamine on proliferation was in part mediated through the stimulation of the H 4 receptor with the induction of G0/G1 phase of the cell cycle arrest, accelerated cell senescence and melanogenesis (Massari et al ., 2011, 2013, 2017). Interestingly, in vivo treatment with histamine and also a specific H 4 agonist, JNJ28610244, not only demonstrated a reduction in the development and growth of human 1205Lu tumours in nude mice but also reduced their metastatic spread and angiogenesis (Massari et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, на фоне роста меланомы изначально низкий уровень гистамина головного мозга увеличивался до интактных значений (+uPA) мышей. Хотя существует ряд исследований, описывающих действие гистамина как модулятора пролиферации некоторых опухолей, его роль в этиопатогенезе злокачественной меланомы до сих пор не доказана [10]. Похоже, что влияние гистамина на пролиферацию опухоли зависит от типа клеток, баланса между различными подтипами рецепторов, концентрацией гистамина, достигнутой в опухолевой среде.…”
Section: Discussionunclassified
“…Установлено, что серотонин индуцирует меланогенез в клетках меланомы кожи SK-MEL-2 и B16/F10 [8,18]. Рецептор гистамина HR4 играет решающую роль в регуляции пролиферации и прогрессировании меланомы человека, поэтому считается, что гистамин может использоваться в комбинированной терапии для повышения эффективности при ее лечении [9,10]. Высокая концентрация катехоламинов в зоне роста злокачественных опухолей на ранних стадиях канцерогенеза, так же как и в период эмбрионального развития, способствует выживанию и пролиферации неопластических клеток в условиях гипоксии [5].…”
unclassified